TRANSFORMING DISTANCE LEARNING SYSTEMS AT G.S. RAKOVSKI NATIONAL DEFENSE COLLEGE IN THE CONTEXT OF NATO'S EVOLVING SECURITY ENVIRONMENT - Petko DIMOV (Journal of Defense Resources Management)
This article provides a comprehensive analysis of how Rakovski National Defence College has adapted its distance learning systems to meet the demands of NATO's evolving security environment, particularly in response to the COVID-19 pandemic and the ongoing war in Ukraine. The study examines the integration of advanced distributed learning (ADL) systems, emphasizing the academy's proactive measures in enhancing cybersecurity and maintaining educational continuity. Through a detailed exploration of security incidents and the implementation of user training programs, the article offers valuable insights for military educators and policymakers on the challenges and strategies associated with digital transformation in military education.